ISSUES OF STATISTICAL ESTIMATION OF BANK’S ADVERTISING ACTIVITY - Elena A. Egorova; Andrey A. Romanov (Статистика и экономика, 2016)
The article offers methodological approach to the analysis of advertising activity of banks who allows to reveal the most effective advertising strategy to provide their high efficiency, to establish correlation connection of the size of advertising budgets with the main social and economic characteristics of bank’s activity.